Impact of COVID-19 Pandemic on Medical Education: Challenges and Opportunities for Medical educators in South Asia - Piryani, Rano Mal; Piryani, Suneel; Piryani, Shomeeta; Shankar, P. Ravi; Shakya, Dhana Ratna (Journal of BP Koirala Institute of Health Sciences, 2020)
Corona virus disease-19 (COVID-19) is an acute highly infectious disease primarily involving the respiratory system. The World Health Organization (WHO) declared COVID-19 a global pandemic on March 11, 2020. No proven efficacious drug and no vaccine are available so far for treatment or prophylaxis of COVID-19. Social distancing has been one of the major measures adopted to prevent spread of the disease. Educational institutions have been shut down all over the world for the safety of both students and communities. Social distancing measures hamper students from assembling in learning labs, lecture halls, or small-group rooms and interacting in person. The major response to the pandemic has been to try to move both teaching-learning and assessment online. Schools have also tried to move clinical learning and teaching communication skills online using standardized patients and facilitators. Online education and assessment are not without their challenges, more so in South Asia. Online teaching learning has been a challenge for both faculty members and students, in varying extent. With online learning environments, supervision and support by the teacher may be less and students should have well developed self-regulated learning skills. These challenges have also offered several opportunities, some general to educators, some relatively specific to medical educators, some global in perspective and some local ones. The pandemic offers both educators and students the insight into: how health problems particularly infectious diseases can affect human life and livelihood; and understanding how people respond to it. The pandemic has forced changes in education methods, modality and process, which though may demand extra effort initially, provides teacher, faculty and facilitator the impetus to keep pace with current trends InTechnology. It has offered an opportunity to move to online learning and interaction and use virtual platforms for e-conference, webinars, podcasts, e-class/ e-lectures etc. Pandemic has brought very rapid changes in educational approaches in South Asia, which otherwise would have taken 5-10 years under normal circumstances.